Immediate and sustained changes in tongue movement with an experimental palatal Fistula: A case study - Marino, Viviane Cristina de Castro [UNESP]; Williams, W. N.; Wharton, P. W.; Paulk, M. F.; Dutka-Souza, JCR; Schulz, G. M. (Alliance Communications Group Division Allen Press, 2005)
Objective: To determine the immediate and longer-term effect(s) on tongue movement following the placement of an experimental opening through a palatal obturator (replicate of subject's prosthesis) worn by an adult male with an unrepaired cleft of the hard and soft palate.Methods: Tongue movements associated with an anterior experimental opening of 20 mm(2) were examined under three conditions: a control condition in which the subject wore the experimental obturator completely occluded, a condition immediately after drilling the experimental openings through the obturator, and a condition after 5 days in which the subject wore the experimental obturator with the experimental opening. An Electromagnetic Articulograph was used for obtaining tongue movements during speech.Results: the findings partly revealed that the immediate introduction of a perturbation to the speech system (experimental fistula) had a temporary effect on tongue movement. After sustained perturbation (for 5 days), the system normalized (going back toward control condition's behavior). Perceptual data were consistent with kinematic tongue movement direction in most of the cases.Conclusions: Although the immediate response can be interpreted as indicative of the subject's attempts to move the tongue toward the opening to compensate for air loss, the findings following a sustained perturbation indicate that with time, other physiological adjustments (such as respiratory adjustments, for example) may help reestablish the requirements of a pressure-regulating system.
Keywords: experimental palatal opening; motor adaptation; palatal fistula; tongue kinematics